Revisiting the Carneiradas: the brothers Machado Rios and the political disputes in Pernambuco (1834-1835) - Cavalcanti Junior, Manoel Nunes (2015)
The impact of the abdication of Pedro I in Pernambuco caused a overturn in the provincial politics, generating new conflicts between the factions struggling for local power. The Carneiradas, that occurred in 1835, were a repercussion of this dispute. The objective of this article is to analyze the Carneiradas from the perspective of the fight between the province's political factions, trying to identify what they reveal about the elements which characterizes the relationship between the political elites of that time.